Estructura de la familia de origen de un grupo de hombres diagnosticados con esquizofrenia residentes en la ciudad de buenaventura (2014)
Objective. This study proposed a general way to describe the structure of the family of origin of three men diagnosed with Schizophrenia, residents in the city of Buenaventura. Addressing limits the types of intra and extra-family home in the family level, family type of family of origin and finally established patterns of interaction both in the marital subsystem and the parent-child dyad in the family origin. Method. This was a qualitative descriptive study of interpretive and transversal nature, based on detailed interviews with three men over 20 years old, diagnosed with schizophrenia. Results. Regarding intrafamiliar diffuse limits and permeable limits were found because of the lack of differentiation between them and their families, generating little autonomy and independence on a personal level. A level extra-rigid boundaries were found, which is solitary families with few support networks. As for the type of family amalgamated families caused by the high level of symbiosis among its members were found. Regarding interaction patterns, were perceived spousal few channels of communication that led to the deadening both marital dyad, and the parent-child subsystem. Conclusions. Perceived in all cases where family structures relational level, the level of cohesion showed polarized: very diffuse or very rigid limits, which makes the system functionality is affected by the effects produced itself, this is devitalization of marital dyad, the loss of personal autonomy and independence, parentalizacion of children, triangular relationships, etc.